Evidence of bhellar (Trewia nudiflora) seed dispersal by chital (Axis axis) in Chitwan National Park, Nepal - Khadka, Bed Bahadur; Lamichhane, Babu Ram (Nepalese Journal of Zoology, 2020)
In riverine forest of Chitwan National Park, Nepal, Bhellar or trewia (Trewia nudiflora) is one of the most abundant tree species. Similarly, chital (Axis axis) is the most abundant and widely distributed deer species. We documented the potential role of chital in seed dispersal of trewia tree in Chitwan. We observed the trewia seeds regurgitated by chital at the Gharial Conservation and Breeding Center (GCBC), Kasara, Chitwan. The trewia seeds were recorded the following morning of the chital sheltering the GCBC. A detailed study is suggested to understand trewia the seed germination success and trewia-chital relationship.